The Role Of Pesantren In Realizing Multicultural Citizenship In Society Through Multicultural Education - Wahono, Margi; Fegiano Wulung Alami; Giri Harto Wiratomo (Universitas Negeri Surabaya, 2025)
This article discusses the role of pesantren in realizing the values of multicultural citizenship that live and develop within Indonesian society through multicultural education. Pesantren, as one of the educational institutions and centers of Islamic religious teaching, has a very urgent role in maintaining and creating the unity and integrity of the nation. Religious, ethnic, linguistic, and cultural diversity is an undeniable reality in Indonesian society. Multicultural-oriented religious education brings a dialogical approach as a means of instilling awareness of living together in diversity and difference. Multiculturalism is not merely the recognition of diversity, but rather an idea or political policy to address and manage cultural diversity and moral, legal, and political claims made in the name of loyalty to ethnicity, religion, language, or nationality. Using a qualitative approach, the author attempts to reveal the role of pesantren in realizing multicultural citizenship within Indonesian society.